2007
DOI: 10.1016/j.jvs.2007.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Compression after sclerotherapy for telangiectasias and reticular leg veins: A randomized controlled study

Abstract: Wearing compression stockings (23 to 32 mm Hg) for 3 weeks enhance the efficacy of sclerotherapy of leg telangiectasias by improving clinical vessel disappearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(76 citation statements)
references
References 10 publications
2
60
1
10
Order By: Relevance
“…This result seems to contradict those found in the literature, which attribute an anti-inflammatory action to compression therapy 10,21 . The result of this research, however, showed that the size of the thrombus had a positive and significant relationship with the inflammatory intensity, and also that the degree of vein obstruction by the thrombus was not significantly different in the various compression periods.…”
Section: Correlation Between the Inflammatory Intensity And Size Of Tcontrasting
confidence: 88%
“…This result seems to contradict those found in the literature, which attribute an anti-inflammatory action to compression therapy 10,21 . The result of this research, however, showed that the size of the thrombus had a positive and significant relationship with the inflammatory intensity, and also that the degree of vein obstruction by the thrombus was not significantly different in the various compression periods.…”
Section: Correlation Between the Inflammatory Intensity And Size Of Tcontrasting
confidence: 88%
“…Those with untreated incompetent saphenous veins have the highest rate of recurrence. 295, 328 Kern et al 329 reported results of liquid sclerotherapy of telangiectasia and reticular veins in 96 patients. Those who wore elastic stockings for 3 weeks after treatment had an early success rate of 76%.…”
Section: Sclerotherapymentioning
confidence: 99%
“…25,26 For example, compression after sclerotherapy has been shown to reduce the formation of thrombi and to prevent pigmentation and matting by minimizing inflammation and angiogenesis. 27 However, one study that randomly assigned 60 pa tients to wear graduated compression stockings for three weeks or to go without compression after ultrasoundguided foam sclerotherapy found no difference in efficacy, adverse effects, satisfaction scores, symptoms and quality of life between the two groups. 26 We found no evidence that one form of compression was better than another, although graduated compression stockings may be better accepted by patients than bandages.…”
Section: Postsurgical or Interventional Treatment Of Varicose Veinsmentioning
confidence: 99%